Case Report: One-stop procedure for atrial fibrillation patients with dextrocardia - Lin Chungyun; Cui Kaijun (Frontiers in Cardiovascular Medicine, 2024)
We present the case of an elderly woman with congenital dextrocardia who experienced severe palpitations. An electrocardiogram revealed paroxysmal atrial fibrillation, and her medical history unveiled cerebral infarction and renal failure. In the treatment of paroxysmal atrial fibrillation, anticoagulation is a key requirement. Although non-vitamin K antagonist oral anticoagulants are recommended by guidelines, their efficacy is compromised in patients undergoing dialysis due to renal metabolism. In addition, warfarin may cause fluctuations in international normalized ratio, which is not conducive to controlling symptoms of cerebral infarction. To improve the patient's quality of life, we focused on addressing the unique challenges posed by dextrocardia in a one-stop procedure.